Analisis Strategi Pemasaran pada Produk Wickercane - Afifah, Alya Noor; Hasmarini, Maulidiyah Indira (Universitas Muhammadiyah Surakarta, 2026)
The purpose of this study is to discuss the analysis of marketing strategies for wickercane products, a rattan-based handicraft business that has high aesthetic value and is environmentally friendly, so that it is increasingly in demand in the global market. This study aims to identify and analyze effective marketing strategies to increase product competitiveness in local and international markets, and to be able to recommend business actors to implement integrated marketing strategies in order to achieve sustainable growth. Thus, it is hoped that rattan handicraft products can be better known and in demand by consumers in various market segments.